Histoire de l'empire Byzantin - Vasilyev, Aleksandr Aleksandroviç, 1867-1953. (Paris)
2 cilt (1. c. ix, 498, [1] sayfa, xvi sayfa resim ; 2. c. 482, [1] sayfa, sayfa xvii-xxvii resim, [7] sayfa harita)